Digital Watermarking in Color Image Based On Joint Between DCT and DWT - Ismail, Jasim Mohammed Salih (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The massive distribution and development in the digital images field with friendly software, that leads to produce unauthorized use. Therefore the digital watermarking as image authentication has been developed for those issues. In this paper, we presented a method depending on the embedding stage and extraction stag. Our development is made by combining Discrete Wavelet Transform (DWT) with Discrete Cosine Transform (DCT) depending on the fact that combined the two transforms will reduce the drawbacks that appears during the recovered watermark or the watermarked image quality of each other, that results in effective rounding method, this is achieved by changing the wavelets coefficients of selected DWT sub bands (HL or HH), followed by applying DCT transform on the selected sub band’s coefficients, this method focuses on the invisibility for the embedded watermark bits, and the quality for the watermarked image; furthermore it focuses on a subjective for the recovered watermark after extraction stage. The proposed method was evaluated by using simple image quality matrix illustrated in the results, and it was found that the proposed method provide good objective quality, the recovered watermark extracted successfully and the quality of recovered watermark are survived.